2018
DOI: 10.1186/s13018-018-0860-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the key genes and pathways of side population cells in human osteosarcoma using gene expression array analysis

Abstract: BackgroundHuman osteosarcoma (OS) is one of the most common primary bone sarcoma, because of early metastasis and few treatment strategies. It has been reported that the tumorigenicity and self-renewal capacity of side population (SP) cells play roles in human OS via regulating of target genes. This study aims to complement the differentially expressed genes (DEGs) that regulated between the SP cells and the non-SP cells from primary human OS and identify their functions and molecular pathways associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…To understand the identified proteins involvement in various biological processes (BPs) and their molecular functions (MFs), along with the protein categories and cellular components (CCs) an international standardized gene function classification system of gene-ontology(GO) (http://www. geneontology.org/), and the DAVID (http://david.abcc.ncifcrf.gov/) (Database Annotation Visualization, and Integrated Discovery) database for functional analysis were performed [63][64][65][66] . For evaluate the protein-protein interactions among the identified proteins from OGS untreated Vs. treated we further analyzed our results using protein-protein interaction (PPI) networks with STRING (Search Tool for the Retrieval of Interacting Genes/ Proteins, Version 9.1) networks (website: http://string-db.org/) and specified high score of 0.09 along with the default parameters for the significant results.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…To understand the identified proteins involvement in various biological processes (BPs) and their molecular functions (MFs), along with the protein categories and cellular components (CCs) an international standardized gene function classification system of gene-ontology(GO) (http://www. geneontology.org/), and the DAVID (http://david.abcc.ncifcrf.gov/) (Database Annotation Visualization, and Integrated Discovery) database for functional analysis were performed [63][64][65][66] . For evaluate the protein-protein interactions among the identified proteins from OGS untreated Vs. treated we further analyzed our results using protein-protein interaction (PPI) networks with STRING (Search Tool for the Retrieval of Interacting Genes/ Proteins, Version 9.1) networks (website: http://string-db.org/) and specified high score of 0.09 along with the default parameters for the significant results.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…12 In osteosarcoma, previous studies showed that side population (SP) of cells, exhibiting increased sphere-forming capabilities and higher tumorigenicity, may be enriched in the cancer stem cells population. 13 Moreover, CD117 and Stro-1 double-positive osteosarcoma cells showed high invasiveness, drug resistance, and a potential for self-renewal and metastasis. 14 In addition to surface markers, there is an increasing interest in the key signaling pathways in osteosarcoma cancer stem cells for the development of new therapies that aim to eliminate these cells.…”
Section: Introductionmentioning
confidence: 99%